The Dionysian signs in Richard Wagner's Tannhäuser - Sanna Iitti (Muzikološki Zbornik, 2015)
The article discusses Dionysian signs in Richard Wagner's opera Tannhäuser und der Sängerkrieg auf Wartburg, focusing on Venus's arietta “Geliebter! Komm”. The method exemplifies musical topics' semiotic analysis. It is proposed that the arietta's pastoral style constitutes a lyric Dionysian sign.